Open source software and the algorithm visualization community - Cooper, Matthew L.; Shaffer, Clifford A.; Edwards, Stephen H.; Ponce, Sean P. (Science of computer programming, 2014)
Algorithm visualizations are widely viewed as having the potential for major impact on computer science education, but their quality is highly variable. We report on the software development practices used by creators of algorithm visualizations, based on data that can be inferred from a catalog of over 600 algorithm visualizations. Since nearly all are free for use and many provide source code, they might be construed as being open source software. Yet many AV developers do not appear to have used open source best practices. We discuss how such development practices might be employed by the algorithm visualization community, and how they might lead to improved algorithm visualizations in the future. We conclude with a discussion of OpenDSA, an open-source project that builds on earlier progress in the field of algorithm visualization and hopes to use open-source procedures to gain users and contributors. •We review the open source practices used on algorithm visualizations (AVs).•The state of the practice for open-source AVs is poor.•Practical obstacles to open-source techniques on e-learning software are discussed.•Solutions to these obstacles are presented.•Community building and sharing will improve practices for e-learning developers.